Rancang Bangun Aplikasi Pendeteksi Titik Koordinat Frekuensi Lightning Whistler - M Weking, Philipus Novenando; Bayupati, I Putu Agung; Piarsa, I Nyoman (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 7, No. 3 Desember 2016DO - 10.24843/LKJITI.2016.v07.i03.p07, 2016)
Unusual activities of earth can be seen by human on a certain time caused by some earth activities change. One of them is the phenomena on atmosphere namely Lightning Whistler. Lightning Whistler is an electromagnetic wave that happens after a lighting on the magnetosphere and ionosphere, where a sound like a whistle is produced. This wave that traverse on radio frequency is called as whistler wave. This research proposed an application for detecting the frequency coordinate of a lightning whistler. The proposed application used STFT, image processing, and morphology image. STFT method is used to convert audio data into spectrogram image data. Afterwards, spectrogram image is processed by using image processing method to reduce noise. Finally, morphology image method is implemented to thicken the whistler wave signal to simplify the detection of coordinate. The proposed application can detect coordinate of a whistler wave signal, in the form of coordinate location, and the number of detected signal, based on time and period.